Sea Country Issue 10 2003 - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 2003)
The tenth issue of Sea Country is written by staff of the Department of Environment (DOE), the Great Barrier Reef Marine Park Authority (GBRMPA) and Community Rangers of Cape York. If you have any questions contact one of the people listed below.
Keywords: Planning; Aboriginal communities; People and the Reef; Traditional owners